EVALUASI KINERJA UNDANG-UNDANG No. 2 TAHUN 1992 TENTANG USAHA PERASURANSIAN SETELAH DUA DEKADE DIUNDANGKAN (1992-2012) - Mulyadi Nitisusastro (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
The Republic of Indonesia’s Law, No. 2 Year 1992 on Insurance Business, that regulates the insurance world in Indonesia had been acted by The Government almost around two decade. How far the performance of the regulation to trigger progress to this sector to day, will be showed through data and information collected from various sources. In-line with its level of explanation this research, its aim to descript about how far were the progress of the Indonesian Insurance industry after twenty years the Law No.2/1992 was acted.This evaluation were purposed to evaluate the progress of insurance bisnis and its aspect during the periode by comparing 2010’s data and the previous one. The result from 1991 until 2010, found that the contribution of Gross Insurance Premium to Gross Domestic Product was increase from 1,24% up to 1,95%. Meanwhile during in the same period the progress of Policy Holders in The Life Insurance Industry was increase from 9.220.103 up to 34.564.028 or growth by 274,88 %. Gross Premium from Rp. 2.665,60 bio up to Rp. 125.116,4 bio. Total assets from Rp. 7.880,60 bio up to Rp. 405.231,0 bio. Total Investment from Rp. 6.276,60 bio up to Rp. 356.393,5 bio. Underwriting result incoming reinsurance from deficit Rp. 5.165 mio up to surplus Rp. 487.573,4 mio. Underwriting result outgoing reinsurance from deficit Rp. 277.355 up to deficit Rp. 4.711.168,1 mio. Key word: insurance business, gross premium, reinsurance